Internalisasi Nilai-Nilai Keagamaan dalam Membentuk Komunikasi Keluarga Islami di Era Digital - Ditha Prasanti; Kismiyati El Karimah (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
Family communication is a communication process experienced by every individual in the life of his family. Every good family will want to provide the best education and care for their children. It even manifests itself based on religious values in the family communication process. Religion is certainly the main foundation, not only in family communication, but in every aspect of human life. In this digital era, every family also has its own way in building religious values that are established through the process of family communication islamic. Therefore, the authors raised this research with the title